A MOF@PS@HAC composite adsorbent, preparation method and application
By combining MOF, PS and HAC to form a multi-stage core-shell structure MOF@PS@HAC composite adsorbent, the problem of difficulty in adsorbing multiple AMCs at the same time in the prior art is solved, and efficient and stable adsorption effects of multiple AMCs are achieved.
Patent Information
- Application Number
- CN202510155991.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-12
- Publication Date
- 2025-04-04
AI Technical Summary
The existing adsorption technology is difficult to efficiently adsorb a variety of air molecular pollutants (AMCs) at the same time, which limits its promotion in semiconductor industrial applications.
Using MOF@PS@HAC composite adsorbent, a composite material with a multi-stage core-shell structure is formed by combining metal organic frame material (MOF) with sulfonated styrene resin (PS) and hydrophobic modified activated carbon (HAC). This material achieves efficient adsorption of various AMCs through strong interactions of MOF, acid-base neutralization reaction of PS and adsorption sites of HAC.
It achieves high-efficiency adsorption and high adsorption capacity for a variety of AMCs, improves adsorption filtration efficiency, and has good adsorption stability, making it less likely to cause structural damage or adsorbent shedding.
Smart Images

Figure CN119746832A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of composite adsorbents, and in particular to a MOF@PS@HAC composite adsorbent, a preparation method and application thereof. Background Art
[0002] With the rapid development of semiconductor manufacturing technology, clean rooms have increasingly stringent control requirements for airborne molecular contaminants (AMC). The main sources of AMC include volatilization of process chemicals, equipment emissions, and the entry of pollutants from the external environment. Its composition is complex and diverse, mainly including acidic gases (such as SO2, HCl), alkaline gases (such as NH3) and volatile organic compounds (such as toluene). AMC not only corrodes key production equipment such as photolithography machines and etching equipment, but also causes surface contamination of silicon wafers and process defects, thereby affecting the yield and performance of the product. Therefore, adsorption technology for efficient removal of AMC has become a focus of attention in the semiconductor industry.
[0003] However, the existing adsorption technology has many defects, which restricts its practical application effect. Existing adsorption materials have made breakthroughs in the adsorption performance of specific types of AMC gases, but it is difficult to achieve efficient adsorption of multiple AMC gases at the same time. For example, activated carbon is widely used in gas adsorption filtration due to its high specific surface area and large pore size distribution. Patent KR1020170133656A achieves effective adsorption of SO2 by combining activated carbon with iron and zinc metal oxides. However, due to the lack of functional sites on the surface of activated carbon itself, efficient adsorption of multiple AMCs cannot be achieved simultaneously through post-modification treatment alone. Unlike activated carbon, ion exchange resin is a polymer material composed of a cross-linked polymer skeleton and active functional groups, and its surface contains a large number of exchangeable anionic and cationic groups. Through ion exchange reactions, the resin can selectively remove charged ion pollutants in the air, such as NH4 + or SO3 2- etc., but it is difficult to capture non-polar molecules with stable chemical properties such as toluene. Metal-organic framework materials (MOFs) have received widespread attention in the field of gas adsorption due to their extremely high specific surface area, flexible and adjustable pore size, and rich chemical modification capabilities. By rationally designing the combination of metal nodes and organic ligands, MOFs can produce strong forces with specific gas molecules, thereby achieving selective adsorption. In patent CN118185037A, 1,4-di(1H-pyrazol-4-yl)benzene (H2BDP) is used as a ligand and copper chloride (CuCl2) is used as a metal center to construct a MOF material with a macroporous structure for efficient adsorption of NH3. However, MOF materials are still unable to efficiently adsorb multiple gaseous pollutants at the same time, limiting their further promotion in semiconductor industrial application scenarios.
[0004] In view of this, it is necessary to develop a super filtration adsorbent material that exhibits high adsorption efficiency and high adsorption capacity for a variety of AMCs to meet the stringent requirements of the semiconductor industry for clean room purification. Summary of the invention
[0005] In view of the deficiencies in the prior art, the present invention provides a MOF@PS@HAC composite adsorbent, a preparation method and an application thereof, which solve the above-mentioned problems.
[0006] To achieve the above objectives, the present invention is implemented through the following technical solutions:
[0007] A method for preparing a MOF@PS@HAC composite adsorbent comprises the following steps:
[0008] Step 1, preparation of hydrophobically modified activated carbon:
[0009] Step 1.1: Select coconut shell activated carbon with high specific surface area and suitable particle size for pretreatment;
[0010] Step 1.2: 20 to 100 mL of organosilane as a hydrophobic modification reagent, 50 to 200 mL of anhydrous ethanol as a solvent, and 5 to 20 mL of acetic acid as a catalyst are measured and uniformly mixed in a ratio of 1 to 5:10:1 to obtain a modification reaction solution A;
[0011] Step 1.3: slowly add 30-250 g of pretreated activated carbon to the modified reaction solution A, place the reaction system in a water bath at 60-120° C., and stir the reaction with magnetic stirring at 300-900 rpm for 2-8 hours;
[0012] Step 1.4: The activated carbon particles are separated by vacuum filtration, and are repeatedly washed with anhydrous ethanol and deionized water for 3 to 5 times, and dried in a vacuum environment at 80 to 120° C. for 8 to 24 hours to obtain a hydrophobically modified activated carbon core, i.e., HAC;
[0013] Step 2, preparing a styrene resin intermediate layer:
[0014] Step 2.1: 60-150 mL of sodium styrene sulfonate and 5-40 mL of divinylbenzene are measured and uniformly mixed to obtain an oil phase solution B;
[0015] Step 2.2: Weigh 2-30 g of the dispersant and dissolve it in 200-800 mL of deionized water to prepare an aqueous solution C with a mass volume concentration of 0.75-6%;
[0016] Step 2.3: Add the oil phase solution B to the water phase solution C under mechanical stirring at 200-600 rpm, and heat to 60-100° C. to obtain a prepolymer solution D;
[0017] Step 2.4: Weigh 20-250 g HAC and 0-5 g compatibilizer and evenly disperse them in the prepared prepolymer solution D, and form a uniform suspension under mechanical stirring at 200-600 rpm;
[0018] Step 2.5: Slowly add 2-10 g of initiator to the suspension, maintain the stirring speed unchanged, and continue the reaction at 60-100° C. for 3-12 h to allow sodium styrene sulfonate and divinylbenzene to polymerize on the surface of the activated carbon core to form a sulfonated styrene resin activated carbon core-shell structure;
[0019] Step 2.6: After the reaction is completed, the reaction product is separated by vacuum filtration, and the product is repeatedly washed 4 to 6 times with deionized water to remove the unreacted monomers and impurities remaining on the surface. The washed core-shell structure particles are dried at a temperature of 60 to 150° C. for 2 to 18 hours to obtain a styrene resin intermediate layer, namely PS@HAC;
[0020] Step 3, preparation of MOF@PS@HAC composite adsorbent:
[0021] Step 3.1: Weigh 10-120 g of an organic ligand and dissolve it in 50-500 mL of an organic solvent under magnetic stirring to obtain a ligand solution E;
[0022] Step 3.2: Weigh 5-60 g of metal salt and dissolve it in 50-500 mL of organic solvent under magnetic stirring to obtain metal salt solution E;
[0023] Step 3.3: Weigh 20-250 g of PS@HAC and dissolve it in the metal salt solution E under magnetic stirring so that the metal ions are firmly loaded on the surface of PS@HAC to obtain a suspension F;
[0024] Step 3.4: under the action of magnetic stirring at 300-1000 rpm, slowly add the ligand solution E to the suspension F, add 0-5 g of nucleating agent, and react at 60-240° C. for 2-36 h;
[0025] Step 3.5: After the reaction is completed, the reaction product is separated by vacuum filtration, and the product is repeatedly washed 4 to 6 times with deionized water to remove unreacted monomers and impurities remaining on the surface. The washed core-shell structure particles are dried at a temperature of 60 to 150°C for 2 to 18 hours to obtain a MOF@PS@HAC composite adsorbent with a multi-level core-shell structure.
[0026] Preferably, the surface area of the coconut shell activated carbon selected in step 1.1 is in the range of 1200 to 1500 m 2 / g, particle size range is 20~60 mesh.
[0027] Preferably, the pretreatment method in step 1.1 is to rinse the coconut shell activated carbon with deionized water three times, and then place it in a vacuum drying oven at 100-150° C. for pretreatment for 2-4 hours to remove impurities and moisture that may exist on the surface of the activated carbon to ensure the purity and activity of the activated carbon.
[0028] Preferably, the organosilane in step 1.2 is one or more of tridecafluorooctyltriethoxysilane (FAS-13), trifluoropropyltrimethoxysilane (TFPS), octyltriethoxysilane (OTES), ethyltriethoxysilane (ETES), methyltrimethoxysilane (MTMS), 3-glycidyloxypropyltrimethoxysilane (GPTMS), 2-(3,4-epoxycyclohexane)ethyltrimethoxysilane (ECHTES), 3-aminopropyltriethoxysilane (APTES), N-(2-aminoethyl)-3-aminopropyltrimethoxysilane (AEPTS), and hydroxyl-terminated polydimethylsiloxane (PDMS-OH).
[0029] Preferably, the dispersant in step 2.2 is one or more of sodium carboxymethyl cellulose (CMC), polyvinyl pyrrolidone (PVP), polyvinyl alcohol (PVA), sodium dodecylbenzene sulfonate (SDBS) and gelatin.
[0030] Preferably, the compatibilizer in step 2.4 is one or more of styrene-maleic anhydride copolymer (SMA), styrene-acrylate copolymer (SAA), styrene block copolymer (SBS) and maleic anhydride grafted styrene elastomer (SEBS-g-MAH), and the initiator in step 2.5 is one or more of azobisisobutyronitrile, azobisisoheptanenitrile, dimethyl azobisisobutyrate hydroperoxide, ammonium persulfate, potassium persulfate, benzoyl peroxide, tert-butyl benzoyl peroxide, and methyl ethyl ketone peroxide.
[0031] Preferably, the organic ligand in step 3.1 is one of imidazole ligands (such as 2-methylimidazole, benzimidazole), pyridine ligands (such as 4-methylpyridine, 2,2'-bipyridine, etc.), amine ligands (such as ethylenediamine, diethylenetriamine, etc.) and polydentate ligands (such as 2,4,6-tris(4-pyridyl)-1,3,5-triazine, 1,3,5-tris(4-aminophenyl)benzene, 2-aminoterephthalic acid, etc.), and the metal salt in step 3.2 is zinc salt (Zn(NO3)2·6H2O, ZnSO4·7H2O, Zn(CH3COO)2·2H2O), cobalt salt (Co(NO3)2· 6H2O, CoSO4·7H2O, CoCl2·6H2O), copper salts (Cu(NO3)2·3H2O, CuCl2, Cu(CH3COO)2·H2O), iron salts (Fe(NO3)3·9H2O, FeCl3·6H2O), titanium salts (TiCl4, TiOCl2), aluminum salts (Al(NO3)3·9H2O, AlCl3), zirconium tetrachloride (ZrCl4) and chromium trichloride hexahydrate (CrCl3·6H2O), and the organic solvent in step 3.1 and step 3.2 is one of deionized water, methanol, ethanol, DMAc and DMF.
[0032] Preferably, the nucleating agent in step 3.4 is one or more of hydrogen chloride, sodium hydroxide, polyvinyl alcohol, sodium dodecylbenzene sulfonate, and polyvinyl pyrrolidone.
[0033] The present invention also provides a MOF@PS@HAC composite adsorbent, which is prepared by the preparation method of the MOF@PS@HAC composite adsorbent.
[0034] The present invention also provides the application of the MOF@PS@HAC composite adsorbent in the field of treating various air molecular pollutants.
[0035] Beneficial Effects
[0036] The present invention provides a MOF@PS@HAC composite adsorbent, a preparation method and an application thereof. Compared with the prior art, the present invention has the following beneficial effects:
[0037] (1) The MOF@PS@HAC composite adsorbent prepared by the present invention has a full range of adsorption types: when the composite adsorbent comes into contact with a mixed gas containing a variety of AMCs, the acidic gas molecules interact strongly with the basic functional groups such as amino groups on the surface of the MOF crystals, fixing them on the surface or in the pores of the MOF material; while the alkaline gas reacts with the sulfonic acid groups on the middle layer resin to undergo an acid-base neutralization reaction; VOCs such as toluene continue to diffuse rapidly along the pore structure of the resin, combining with the adsorption sites on the surface of the core layer activated carbon, and ultimately achieving efficient adsorption of a variety of AMCs.
[0038] (2) The MOF@PS@HAC composite adsorbent prepared by the present invention has high adsorption efficiency: based on the differences in pore structure and chemical properties of each layer of material, a gradient environment is formed that is conducive to the diffusion and adsorption of gaseous pollutants. Driven by the concentration gradient, the gas molecules diffuse rapidly. The pore connectivity and hierarchical structure of each layer reduce the diffusion resistance, and can quickly migrate between the layers of material and be captured by the adsorption sites, realizing an efficient adsorption mass transfer process, thereby effectively improving the adsorption filtration efficiency.
[0039] (3) The MOF@PS@HAC composite adsorbent prepared by the present invention has a large adsorption capacity: the multi-level core-shell structure enables a synergistic adsorption effect to be formed between the materials of each layer. When the composite adsorbent comes into contact with a mixed gas containing a variety of gaseous pollutants, different gas molecules will preferentially interact with the adsorption sites of the corresponding layer according to their own properties, avoiding the performance degradation caused by competitive adsorption, thereby improving the overall adsorption capacity.
[0040] (4) The MOF@PS@HAC composite adsorbent prepared by the present invention has good adsorption stability: the core-shell structure of the composite adsorbent gives it good adsorption stability, and the layers are tightly combined by chemical bonding or physical coating, so it is not easy for the structure to be damaged or the adsorbent to fall off during the adsorption process. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 It is a dynamic adsorption curve diagram of toluene by the composite adsorbents prepared in Examples 1-3 of the present invention and Comparative Example 1;
[0042] Figure 2 is a graph showing the adsorption capacity of the composite adsorbents prepared in Examples 1-3 of the present invention and Comparative Example 1 for toluene;
[0043] Figure 3 It is a dynamic adsorption curve diagram of NH3 by the composite adsorbents prepared in Examples 1-3 of the present invention and Comparative Example 2;
[0044] Figure 4 It is a graph of the adsorption capacity of NH3 by the composite adsorbents prepared in Examples 1-3 of the present invention and Comparative Example 2;
[0045] Figure 5 It is a dynamic adsorption curve diagram of SO2 by the composite adsorbents prepared in Examples 1-3 of the present invention and Comparative Example 3;
[0046] Figure 6 It is a graph showing the adsorption capacity of the composite adsorbents prepared in Examples 1-3 of the present invention and Comparative Example 3 for SO2. DETAILED DESCRIPTION
[0047] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0048] Embodiment 1:
[0049] Preparation method of MOF@PS@HAC composite adsorbent:
[0050] Step 1, preparation of hydrophobically modified activated carbon:
[0051] Step 1.1: Select a material with high specific surface area (1467m 2 / g) and coconut shell activated carbon with appropriate particle size (40-50 mesh) were rinsed with deionized water for 3 times and then placed in a vacuum drying oven at 120°C for pretreatment for 2.5h to remove possible impurities and moisture on the surface of the activated carbon to ensure the purity and activity of the activated carbon.
[0052] Step 1.2: 40 mL of MTMS as a hydrophobic modification reagent, 160 mL of anhydrous ethanol as a solvent, and 16 mL of acetic acid as a catalyst were measured and uniformly mixed in a ratio of 2.5:10:1 to obtain a modified reaction solution A;
[0053] Step 1.3: 120 g of pretreated activated carbon particles were slowly added to the modified reaction solution A, and the reaction system was placed in a water bath at 80°C and stirred with a magnetic stirrer at 600 rpm for 6 h;
[0054] Step 1.4: The activated carbon particles were separated by vacuum filtration, washed repeatedly with anhydrous ethanol and deionized water for 5 times, and dried in a vacuum environment at 120° C. for 10 h to obtain HAC.
[0055] Step 2, preparing a styrene resin intermediate layer:
[0056] Step 2.1: 100 mL of sodium styrene sulfonate and 15 mL of divinylbenzene were measured and uniformly mixed to obtain an oil phase solution B;
[0057] Step 2.2: Weigh 5 g of CMC and dissolve it in 500 mL of deionized water to prepare an aqueous solution C with a mass volume concentration of 1%;
[0058] Step 2.3: Add the oil phase solution B to the water phase solution C under mechanical stirring at 400 rpm, and heat to 70° C. to obtain a prepolymer solution D;
[0059] Step 2.4: Weigh 120 g HAC and 1.5 g SMA and evenly disperse them in the prepared prepolymer solution D, and form a uniform suspension under mechanical stirring at 400 rpm;
[0060] Step 2.5: Slowly add 5 g of benzoyl peroxide to the suspension, maintain the stirring speed unchanged, and continue the reaction at 80 ° C for 6 h to allow sodium styrene sulfonate and divinylbenzene to polymerize on the surface of the activated carbon core to form a sulfonated styrene resin activated carbon core-shell structure;
[0061] Step 2.6: After the reaction is completed, the reaction product is separated by vacuum filtration and washed repeatedly with deionized water for 5 times to remove the unreacted monomers and impurities remaining on the surface. Finally, the washed core-shell structure particles are dried at 100°C for 12 hours to obtain PS@HAC.
[0062] Step 3, preparation of MOF@PS@HAC composite adsorbent:
[0063] Step 3.1: Weigh 59.112 g of 2-methylimidazole and dissolve it in 400 mL of deionized water under magnetic stirring to obtain ligand solution E;
[0064] Step 3.2: Weigh 26.773 g Zn(NO3)2·6H2O and dissolve it in 400 mL deionized water under magnetic stirring to obtain metal salt solution E;
[0065] Step 3.3: Weigh 120 g of PS@HAC and dissolve it in the metal salt solution E under magnetic stirring so that the metal ions are firmly loaded on the surface of PS@HAC to obtain a suspension F;
[0066] Step 3.4: Under magnetic stirring at 600 rpm, slowly add ligand solution E to suspension F, add 2.5 g of polyvinyl pyrrolidone, and react at 80 °C for 12 h;
[0067] Step 3.5: After the reaction is completed, the reaction product is separated by vacuum filtration and washed repeatedly with deionized water for 5 times to remove the unreacted monomers and impurities remaining on the surface. The washed core-shell structure particles are dried at 100°C for 12 hours to obtain a ZIF-8@PS@HAC composite adsorbent with a multi-level core-shell structure.
[0068] Embodiment 2:
[0069] In step 3.1 of Example 1, 59.112 g of 2-methylimidazole was replaced with 130.435 g of 2-aminoterephthalic acid, and in step 3.2 of Example 1, 26.773 g of Zn(NO3)2·6H2O was replaced with 20.972 g of ZrCl4. The other conditions remained unchanged, and finally the UiO-66-NH2@PS@HAC composite adsorbent was prepared.
[0070] Embodiment 3:
[0071] The 20.972 g ZrCl4 in Example 2 was replaced by 23.981 g CrCl3·6H2O, and the other conditions remained unchanged, and finally the MIL-101-NH2@PS@HAC composite adsorbent was prepared.
[0072] Comparative Example 1:
[0073] Step 1 in Example 1 was omitted, and the activated carbon without hydrophobic modification was directly used as the core, and the other conditions remained unchanged to prepare the ZIF-8@PS@AC composite adsorbent.
[0074] Comparative Example 2:
[0075] The sodium styrene sulfonate in step 2.1 of Example 1 was replaced by styrene, and the other conditions remained unchanged to prepare a ZIF-8@PS@HAC composite adsorbent without sulfonic acid groups.
[0076] Comparative Example 3:
[0077] The 130.435 g of 2-aminoterephthalic acid in step 3.1 of Example 2 was replaced with 119.62 g of terephthalic acid to prepare a UiO-66@PS@HAC composite adsorbent free of amine groups.
[0078] Structural characterization and performance testing:
[0079] 1. Specific surface area and pore size test analysis
[0080] The BET surface area and pore structure of the materials were measured using a Belsorp MAXⅡ analyzer at -195°C using N2 adsorption and desorption. The total surface area was determined using the Brunauer-Emmett-Taylor (BET) equation.
[0081] The test results are shown in Table 1:
[0082] Table 1 Test results of Examples 1-3 and Comparative Examples 1-3
[0083] sample <![CDATA[BET(m 2 / g)]]> <![CDATA[Pore volume (cm 3 / g)]]> Example 1 (ZIF-8@PS@HAC) 1452 0.78 <![CDATA[Example 2 (UiO-66-NH2@PS@HAC)]]> 1820 0.92 <![CDATA[Example 3 (MIL-101-NH2@PS@HAC)]]> 2217 1.22 Comparative Example 1 (ZIF-8@PS@AC) 1046 0.55 Comparative Example 2 (ZIF-8@PS@HAC without sulfonic acid group) 1778 0.88 Comparative Example 3 (UiO-66@PS@HAC) 2171 1.16
[0084] The results show that Examples 1 to 3 all have high specific surface areas and pore volumes. The specific surface area and pore volume of Example 1 are 1452 m 2 / g and 0.78cm 3 / g, and Example 2 are 1820m 2 / g and 0.92cm 3 / g, and Example 3 were 2217m 2 / g and 1.22cm 3 / g. It is worth noting that the BET and pore volume of Comparative Example 1 decreased significantly, which may be because the activated carbon in Comparative Example 1 was not hydrophobically modified, and the surface of the activated carbon still maintained strong hydrophilicity, resulting in poor interfacial compatibility between the oil phase monomer and the hydrophilic surface of the activated carbon during the polymerization of the styrene resin intermediate layer, making it difficult to evenly cover the surface of the activated carbon, thereby affecting the structural integrity of the PS layer.
[0085] 2. Dynamic adsorption performance test
[0086] The material was tested for adsorption of SO2, NH3 and toluene using the UTEST static adsorption device. Initial efficiency: control the test air volume (12L / min), test resistance (100Pa), test concentration (600ppb); pollutant holding capacity: control the test air volume (15L / min), test resistance (100Pa), test concentration (10ppm). The adsorption capacity was calculated using the penetration curve integral, and the formula is as follows:
[0087]
[0088] Where q (g / g) is the maximum adsorption capacity, F (mL / min) is the total gas flow rate, C0 and C (mg / m 3 ) are the inlet and outlet concentrations of toluene, m (g) is the weight of the adsorbent, t s (min) is the adsorption time.
[0089] The test results are as follows Figure 1-6As shown in the figure, the composite adsorbent prepared in the embodiment of the present invention exhibits high adsorption performance for VOCs represented by toluene, acidic gases represented by SO2, and alkaline gases represented by NH3: (1) Compared with the sample ZIF-8@PS@AC in the comparative example 1 in which the activated carbon is not hydrophobically modified, the adsorption penetration time of toluene by the three groups of samples in the embodiments 1, 2, and 3 is significantly delayed, and the adsorption capacity of toluene is increased from 51 mg / g to 177 mg / g, 159 mg / g, and 157 mg / g, respectively; (2) Compared with the sample in the comparative example 2 in which the sulfonic acid group is not grafted, the adsorption capacity of toluene by the three groups of samples in the embodiments 1, 2, and 3 is significantly increased from 51 mg / g to 177 mg / g, 159 mg / g, and 157 mg / g, respectively. The adsorption penetration time of NH3 by the three groups of samples in Examples 1, 2 and 3 was also significantly delayed, and the adsorption capacity of NH3 was increased from 121 mg / g to 218 mg / g, 256 mg / g and 211 mg / g, respectively; (3) Compared with the comparative example 3 sample UiO-66@PS@HAC without constructing Lewis basic sites (i.e., the operation in step 3), the adsorption penetration time of SO2 by the three groups of samples in Examples 1, 2 and 3 was significantly delayed, and the adsorption capacity of SO2 was increased from 315 mg / g to 662 mg / g, 610 mg / g and 527 mg / g, respectively.
[0090] Meanwhile, the contents not described in detail in this specification belong to the prior art known to those skilled in the art.
[0091] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0092] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a MOF@PS@HAC composite adsorbent, characterized in that: The following steps are involved: Step 1, preparation of hydrophobically modified activated carbon: Step 1.1: Select coconut shell activated carbon with high specific surface area and suitable particle size for pretreatment; Step 1.2: 20 to 100 mL of organosilane as a hydrophobic modification reagent, 50 to 200 mL of anhydrous ethanol as a solvent, and 5 to 20 mL of acetic acid as a catalyst are measured and uniformly mixed in a ratio of 1 to 5:10:1 to obtain a modification reaction solution A; Step 1.3: slowly add 30-250 g of pretreated activated carbon to the modified reaction solution A, place the reaction system in a water bath at 60-120° C., and stir the reaction with magnetic stirring at 300-900 rpm for 2-8 hours; Step 1.4: The activated carbon particles are separated by vacuum filtration, and are repeatedly washed with anhydrous ethanol and deionized water for 3 to 5 times, and dried in a vacuum environment at 80 to 120° C. for 8 to 24 hours to obtain a hydrophobically modified activated carbon core, i.e., HAC; Step 2, preparing a styrene resin intermediate layer: Step 2.1: 60-150 mL of sodium styrene sulfonate and 5-40 mL of divinylbenzene are measured and uniformly mixed to obtain an oil phase solution B; Step 2.2: Weigh 2-30 g of the dispersant and dissolve it in 200-800 mL of deionized water to prepare an aqueous solution C with a mass volume concentration of 0.75-6%; Step 2.3: Add the oil phase solution B to the water phase solution C under mechanical stirring at 200-600 rpm, and heat to 60-100° C. to obtain a prepolymer solution D; Step 2.4: Weigh 20-250 g HAC and 0-5 g compatibilizer and evenly disperse them in the prepared prepolymer solution D, and form a uniform suspension under mechanical stirring at 200-600 rpm; Step 2.5: Slowly add 2-10 g of initiator to the suspension, maintain the stirring speed unchanged, and continue the reaction at 60-100° C. for 3-12 h to allow sodium styrene sulfonate and divinylbenzene to polymerize on the surface of the activated carbon core to form a sulfonated styrene resin activated carbon core-shell structure; Step 2.6: After the reaction is completed, the reaction product is separated by vacuum filtration, and the product is repeatedly washed 4 to 6 times with deionized water to remove the unreacted monomers and impurities remaining on the surface. The washed core-shell structure particles are dried at a temperature of 60 to 150° C. for 2 to 18 hours to obtain a styrene resin intermediate layer, namely PS@HAC; Step 3, preparation of MOF@PS@HAC composite adsorbent: Step 3.1: Weigh 10-120 g of an organic ligand and dissolve it in 50-500 mL of an organic solvent under magnetic stirring to obtain a ligand solution E; Step 3.2: Weigh 5-60 g of metal salt and dissolve it in 50-500 mL of organic solvent under magnetic stirring to obtain metal salt solution E; Step 3.3: Weigh 20-250 g of PS@HAC and dissolve it in the metal salt solution E under magnetic stirring so that the metal ions are firmly loaded on the surface of PS@HAC to obtain a suspension F; Step 3.4: under the action of magnetic stirring at 300-1000 rpm, slowly add the ligand solution E to the suspension F, add 0-5 g of nucleating agent, and react at 60-240° C. for 2-36 h; Step 3.5: After the reaction is completed, the reaction product is separated by vacuum filtration, and the product is repeatedly washed 4 to 6 times with deionized water to remove unreacted monomers and impurities remaining on the surface. The washed core-shell structure particles are dried at a temperature of 60 to 150°C for 2 to 18 hours to obtain a MOF@PS@HAC composite adsorbent with a multi-level core-shell structure.
2. The method for preparing a MOF@PS@HAC composite adsorbent according to claim 1, characterized in that: The surface area of the coconut shell activated carbon selected in step 1.1 is in the range of 1200 to 1500 m 2 / g, particle size range is 20~60 mesh.
3. The method for preparing a MOF@PS@HAC composite adsorbent according to claim 1, characterized in that: The pretreatment method in step 1.1 is to rinse the coconut shell activated carbon with deionized water three times, and then place it in a vacuum drying oven at 100-150° C. for pretreatment for 2-4 hours to remove impurities and moisture that may exist on the surface of the activated carbon to ensure the purity and activity of the activated carbon.
4. The method for preparing a MOF@PS@HAC composite adsorbent according to claim 1, characterized in that: The organosilane in step 1.2 is one or more of tridecafluorooctyltriethoxysilane, trifluoropropyltrimethoxysilane, octyltriethoxysilane, ethyltriethoxysilane, methyltrimethoxysilane, 3-glycidyloxypropyltrimethoxysilane, 2-(3,4-epoxycyclohexane)ethyltrimethoxysilane, 3-aminopropyltriethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, and hydroxyl-terminated polydimethylsiloxane.
5. The method for preparing a MOF@PS@HAC composite adsorbent according to claim 1, characterized in that: In the step 2.2, the dispersant is one or more of sodium hydroxymethyl cellulose, polyvinyl pyrrolidone, polyvinyl alcohol, sodium dodecylbenzene sulfonate and gelatin.
6. The method for preparing a MOF@PS@HAC composite adsorbent according to claim 1, characterized in that: The compatibilizer in step 2.4 is one or more of styrene-maleic anhydride copolymer, styrene-acrylate copolymer, styrene block copolymer and maleic anhydride grafted styrene elastomer, and the initiator in step 2.5 is one or more of azobisisobutyronitrile, azobisisoheptanenitrile, dimethyl azobisisobutyrate hydroperoxide, ammonium persulfate, potassium persulfate, benzoyl peroxide, tert-butyl benzoyl peroxide and methyl ethyl ketone peroxide.
7. The method for preparing a MOF@PS@HAC composite adsorbent according to claim 1, characterized in that: The organic ligand in step 3.1 is one of an imidazole-containing ligand, a pyridine-containing ligand, an amine-containing ligand and a multidentate ligand; the metal salt in step 3.2 is one of a zinc salt, a cobalt salt, a copper salt, an iron salt, a titanium salt, an aluminum salt, zirconium tetrachloride and chromium trichloride hexahydrate; and the organic solvent in steps 3.1 and 3.2 is one of deionized water, methanol, ethanol, DMAc and DMF.
8. The method for preparing a MOF@PS@HAC composite adsorbent according to claim 1, characterized in that: In step 3.4, the nucleating agent is one or more of hydrogen chloride, sodium hydroxide, polyvinyl alcohol, sodium dodecylbenzene sulfonate, and polyvinyl pyrrolidone.
9. A MOF@PS@HAC composite adsorbent, characterized in that: The composite adsorbent is prepared by the preparation method of the MOF@PS@HAC composite adsorbent described in any one of claims 1 to 8.
10. Application of the MOF@PS@HAC composite adsorbent according to claim 9 in the field of treating various air molecular pollutants.
Citation Information
Patent Citations
Metal organic framework material of Cu, preparation method and ammonia gas adsorption application
CN118185037A
Iron-zinc complex metal oxide coated activated carbon adsorbent for acidic gas removal and manufacturing method the same
KR1020170133656A
Cited By
Light response type hydrogel composite material and application thereof in pulpitis treatment
CN120284851A
A photoresponsive hydrogel composite material and its application in the treatment of pulpitis
CN120284851B
MOF-based gas adsorbent with core-shell-shell structure as well as preparation method and application of MOF-based gas adsorbent
CN121155535A